PENDEKATAN NILAI DALAM ERA DIGITAL: PENGARUH MODEL VCT DAN MEDIA WORDWALL TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM - Ulfa, Banatul Khoiriah; Anwar, Syaiful; Fauzan, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of the Value Clarification Technique (VCT) learning model integrated with Wordwall media in improving the learning outcomes of eighth-grade students in Islamic Religious Education. A quantitative approach with a quasi-experimental design was employed, involving two classes assigned as experimental and control groups. The data were collected using a multiple-choice test instrument that had undergone validation and reliability testing. The results indicated a significant difference in learning outcomes between the experimental and control groups, with a higher post-test mean score in the experimental group. The VCT model allowed students to clarify values reflectively, while Wordwall enhanced active participation and learning motivation. These findings suggest that integrating value-based approaches with interactive digital media can serve as an effective strategy for delivering contextual and engaging Islamic Religious Education.